A Review on Various Nearest Neighbor Searching Algorithms Using Graphical Processing Units - Jacob, Sneha; Mohamed, Anuj (International Journal of Computer Sciences and Engineering, 2025)
The demand for Graphical Processing Units or GPUs, gained a tremendous hike during the past few years as a result of its migration from processing and representation of mere high dimensional graphical patterns to a heterogeneous high performance computing capability. The future generation data science requirements like Big Data Analysis and Deep Learning increased the popularity of GPUs to a wide extend. Graphical Processing Units or GPUs are well suited for parallel processing which enables visualization of vast amount of real time processed data in a more significant manner than CPU. From processing mere graphical algorithms, GPU has gone through numerous advancements in the past few decades. They can be used to improve the performance and efficiency of any algorithm nowadays. The expenditure of installation and use of GPUs have come down to a great extent from the initial huge amount. Data classification tasks like kNN classification can be done more efficiently and cost effectively by applying parallelism using GPU. kNN algorithms are the most popular data classification algorithm, because of its simplicity, high accuracy and versatility. This paper studies four major kNN algorithms developed for GPU processing and compares the techniques and methodologies used in them